Entropy beyond the second law : thermodynamics and statistical mechanics for equilibrium, non-equilibrium, classical, and quantum systems /: thermodynamics and statistical mechanics for equilibrium, non-equilibrium, classical, and quantum systems. (2018) - Attard, Phil
No abstract available